Digital Literacy and Analytical Thinking in Facing Misinformation during Digital Era: Systematic Literature Review - imanuel leba; Ratna Ekawati; Slamet Arifin (Fakultas Ilmu Pendidikan Universitas PGRI Kanjuruhan Malang, 2024)
This study aims to investigate the critical roles of digital literacy and analytical thinking skills in addressing misinformation challenges in the 21st-century digital era. Using a systematic literature review (SLR) guided by PRISMA methodology, ten peer-reviewed articles published in the last four years were analyzed to provide a comprehensive understanding. The results reveal that deficiencies in digital literacy and analytical thinking increase vulnerability to misinformation, hinder online participation, and limit educational opportunities. Conversely, these competencies empower individuals to evaluate information critically, foster civic engagement, and enhance learning experiences. Technological interventions, such as e-tutorials, project-based learning, and digital storytelling, effectively develop these skills when supported by structured teacher guidance. The study concludes that integrating these skills into educational frameworks is essential to foster resilience against misinformation and nurture informed digital citizens. It advocates for collaborative efforts among educators, policymakers, and technology experts to design adaptive and sustainable learning environments tailored to diverse needs. These insights contribute to the discourse on combating misinformation and preparing individuals for challenges in a rapidly evolving digital landscape.